2022
DOI: 10.3389/fmicb.2022.904189
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Rubella Virus Infection in Immortalized Human First-Trimester Trophoblasts Under Low-Glucose Stress Conditions

Abstract: Rubella virus (RuV) infections in pregnant women, especially first-trimester infections, can lead to congenital rubella syndrome (CRS). However, the mechanisms of fetal RuV infection are not completely understood, and it is not observed in every pregnant woman infected with RuV. As gestational diabetes mellitus is a risk factor for congenital viral infections, we investigated the possible roles of hypoglycemia-related endoplasmic reticulum (ER) stress as a key factor for vertical RuV infection using immortaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Infectious agents, especially ToRCHZ and other viral causative agents, at the maternal–fetal interface are associated with adverse pregnancy outcomes and fetal loss [ 86 , 87 , 88 , 89 ]. Mother-to-child transmission (MTCT) of viruses can occur through multiple routes, including direct transplacental infection with placental damage or disruption of the maternal–fetal barrier (such as CMV, RuV, ZIKV, or HIV), ascending transmission from the vaginal cervical area (HSV), transplacental immune transfer of maternal antibodies which enhances viral infection (ZIKV), perinatal transmission (HIV, HBV), postnatal transmission through breastfeeding (HCMV, HIV, HBV, HSV) [ 55 , 58 , 64 , 76 , 90 , 91 , 92 ] ( Figure 1 and Table 2 ).…”
Section: Viral Infections In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Infectious agents, especially ToRCHZ and other viral causative agents, at the maternal–fetal interface are associated with adverse pregnancy outcomes and fetal loss [ 86 , 87 , 88 , 89 ]. Mother-to-child transmission (MTCT) of viruses can occur through multiple routes, including direct transplacental infection with placental damage or disruption of the maternal–fetal barrier (such as CMV, RuV, ZIKV, or HIV), ascending transmission from the vaginal cervical area (HSV), transplacental immune transfer of maternal antibodies which enhances viral infection (ZIKV), perinatal transmission (HIV, HBV), postnatal transmission through breastfeeding (HCMV, HIV, HBV, HSV) [ 55 , 58 , 64 , 76 , 90 , 91 , 92 ] ( Figure 1 and Table 2 ).…”
Section: Viral Infections In Pregnancymentioning
confidence: 99%
“…It is well established that for most of the CRS cases, the infection and vertical transmission occurred in the first trimester [ 9 ]. However, in vitro studies showed that RuV has low infectivity in trophoblasts and suggest that some factors may affect the infection in the first trimester [ 8 , 13 , 92 , 117 ].…”
Section: Viral Infections In Pregnancymentioning
confidence: 99%